BIOLOGIC WIDTH CONCEPT IN GINGIVECTOMY - Desy Fidyawati (Fakultas Kedokteran Gigi Universitas Prof. Dr. Moestopo (Beragama), 2020)
Background: Relationship between periodontal tissue and aesthetic considerations is an important thing to determine the form, function and aesthetics of periodontal tissue itself. For orthodontic cases with gingival enlargement, using the biological width concept in gingivectomy to facilitate an optimal oral hygiene maintenance, function and aesthetic. Bone sounding before gingival recontouring is dictated by the distance from the gingiva crest to alveolar crest. Recommended distance between margins restoration and alveolar bone crest is 3 mm to avoid breaching the biologic width.Case and Case Management: Case 1: A 21 years old female patient whom referred from orthodontist with gingival enlargement in upper front teeth after treated with fixed orthodontic for 1.5 years. PBI: 1,6. After clinical examination, bone sounding was performed = 7mm and gingivectomy without ostectomy was determined. Case 2: A male patient, 24 years old, with gingival enlargement in upper front teeth while treated with fixed orthodontic. After determined the problem, bone sounding (6 mm) was performed along with gingivectomy without ostectomy also for anterior upper right site.Conclusion: The purpose of this report is to provide a diagnostic rationale for gingival recontouring. When gingivectomy is determined, the concept of biological width must be applied achieve a harmonious gingival contour with an optimal oral hygiene maintenance.